Iterative Soft-Decision Decoding of Binary Cyclic Codes - Baldi, Marco (Array, 2008)
Abstract: Binary cyclic codes achieve good error correction performance and allow the implementation of very simple encoder and decoder circuits. Among them, BCH codes represent a very important class of t-error correcting codes, with known structural properties and error correction capability. Decoding of binary cyclic codes is often accomplished through hard-decision decoders, although it is recognized that soft-decision decoding algorithms can produce significant coding gain with respect to hard-decision techniques. Several approaches have been proposed to implement iterative soft-decision decoding of binary cyclic codes. We study the technique based on "extended parity-check matrices", and show that such method is not suitable for high rates or long codes. We propose a new approach, based on "reduced parity-check matrices" and "spread parity-check matrices", that can achieve better correction performance in many practical cases, without increasing the complexity